Heart failure family-based education: a systematic review. Issue 3 (March 2016) - Srisuk, Nittaya; Cameron, Jan; Ski, Chantal F.; Thompson, David R.
Highlights: Systematic review of HF family-based education found improvements in HF knowledge. Modest improvements in other outcomes were found. Most studies were marred by weak conceptualisation and methodological rigor. Well-designed robust studies of HF family-based education are needed. Abstract: Objective: To systematically review evidence for the efficacy of family-based education for heart failure (HF) patients and carers. Method: A systematic review was conducted. Databases CINAHL, MEDLINE Complete, Cochrane, PubMed, Web of Science, EMBASE, PsycINFO, and Scopus were searched between 1 January 2005 and 1 May 2015. Randomised controlled trials included HF patient and carer dyads or carers alone. The primary outcome was HF knowledge. Secondary outcomes included self-care behaviour, dietary and treatment adherence, quality of life, depression, perceived control, hospital readmissions, and carer burden. Result: Six trials reported in nine papers were included. Wide variation in the quality of the studies was found. Two studies only examined HF knowledge; a significant improvement among patients and carers was reported. Other significant findings were enhanced patient self-care, boosted dietary and treatment adherence, enriched patient quality of life, improved perceived control among patients but not carers, and reduced carer burden Conclusion: Modest evidence was found for family-based education among HF patients and carers. Methodological shortcomings of trials signify the need for empirically sound future research. Practice implication: Family-based HF education needs to include strategies that are tailored to the HF patient and carer, and sustainable in nature.